2016
DOI: 10.1093/mnras/stw796
|View full text |Cite
|
Sign up to set email alerts
|

How unusual is the cool-core radio halo cluster CL1821+643?

Abstract: Massive galaxy clusters with cool-cores typically host diffuse radio sources called minihaloes, whereas, those with non-cool-cores host radio haloes. We attempt to understand the unusual nature of the cool-core galaxy cluster CL1821+643 that hosts a Mpc-scale radio halo using new radio observations and morphological analysis of its intra-cluster medium. We present the Giant Metrewave Radio Telescope (GMRT) 610 MHz image of the radio halo. The spectral index, α defined as S ∝ ν −α , of the radio halo is 1.0 ± 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…A two component radio halo is reported in Abell 2142 and is thus unlike typical mini-halos . The systems Abell 2390, Abell 2261 (Sommer & Basu 2014) and CL1821 + 643 (Bonafede et al 2014;Kale & Parekh 2016) are similar to the radio halo reported here. Recently low brightness and steep spectrum emission has been found surrounding the known mini-halos in the clusters PSZ1G139.61+24.20 (Savini et al 2018) and RXJ1720.1+2638 (Savini et al 2019).…”
Section: Mini-halo To Radio Halo Transition Systemsupporting
confidence: 83%
See 1 more Smart Citation
“…A two component radio halo is reported in Abell 2142 and is thus unlike typical mini-halos . The systems Abell 2390, Abell 2261 (Sommer & Basu 2014) and CL1821 + 643 (Bonafede et al 2014;Kale & Parekh 2016) are similar to the radio halo reported here. Recently low brightness and steep spectrum emission has been found surrounding the known mini-halos in the clusters PSZ1G139.61+24.20 (Savini et al 2018) and RXJ1720.1+2638 (Savini et al 2019).…”
Section: Mini-halo To Radio Halo Transition Systemsupporting
confidence: 83%
“…is the number of beams in the extent of the emission, σ abs is the percentage error on the absolute flux density scale. We used σ abs = 0.1 (e. g. Kale & Parekh 2016) and found N b = 75.6 to get the error of 5 mJy on the 606 MHz flux density of the RH. The K-corrected radio power at frequency ν is…”
Section: Resultsmentioning
confidence: 99%
“…Bonafede et al (2014b) discovered a large 1.1 Mpc radio halo in CL1821+643 which contains a strong cool core. If this halo is caused by a merger event, the cluster is in a stage where the merger has not (yet) been able to disrupt the cool core as also noted by Kale and Parekh (2016). For example, because the merger is an off-axis event, or the merger is still in an early stage.…”
Section: Unificationmentioning
confidence: 88%
“…An example of these outliers is the giant radio halo in the strong cool-core cluster CL 1821+643 (Bonafede et al 2014). A study of the X-ray morphological parameters of this cluster shows that it shares the same properties of galaxy clusters hosting a radio halo, suggesting that it may be a case of a cluster merger in which the cool core has been preserved (Kale & Parekh 2016). More recently, a giant radio halo has been reported in A 2261 and A 2390, neither of which is a major merger (Sommer et al 2016).…”
Section: Introductionmentioning
confidence: 99%